Pengurangan Pemborosan Waktu Produksi Pada Proses Pembuatan Rumah Boneka Menggunakan Pendekatan Lean - tiara tiara (Faktor Exacta, 2018)
CV. Puppet house is a small and medium-sized industrial enterprise and manufactures in producing doll house with wood base material. The purpose of this study is to know the kind of wasted production time on each production process at CV. Puppet house and give repair suggestions so as to increase the productivity of puppet house production time. This study uses a quantitative approach with the processing time of each workstation. This study uses a lean approach with tools value stream mapping (VSM), at the beginning of the study, drawing a current state mapping obtained from observations on puppets CV, then from the image was identified problem of each production process. Then analyze the problem using line balancing to level the cycle time, fishbone diagram to find out the factors causing the problem of the production of puppets and the introduction of waste on each production process. In the current state mapping the spend time of 1418.76 with 10 day lead time. After calculating and equating cycle time by using line balancing. Based on the analysis, there are several causes that can cause waste among others: delay of raw material arrival, physical factors of workers, workers who do not follow the work standards determined by the puppets and movements that are not required but performed by the workers. The proposed repair can be given to the CV of these puppets is to communicate well with the supplier, to conduct training once every 3 months to the employees, providing a special place for storage of raw materials and semi-finished materials and do not turn on television while working.Keywords: Lean Manufacturing, Waste, Value Stream Mapping, Lead Time, Fshbone Diagram, CV. Rumah boneka.